Comparison between infliximab and adalimumab in the treatment of perianal fistulas in Crohn's disease - Santos,Carlos Henrique Marques dos (2014)
Introduction: The fistulizing form of Crohn's disease (CD) represents a great challenge regarding treatment, especially perianal fistulas, for its high prevalence. Objective: To assess factors related to the response to surgical treatment associated with anti-TNF inpatients with CD and perianal fistulas. Method: Retrospective study of patients with CD and perianal fistulas who used IFX or ADA in association with surgical treatment. Results: 30 patients with a mean age of 35 years were studied; 16 were treated with ADA (9 ADA + AZA) and 14 with IFX (10 IFX + AZA); ten of those treated with ADA responded, and of the six non-respondents, only one responded to IFX; eight responded to IFX, and among those non-respondents, no one showed response with ADA; among the respondents, there were 10 men and nine women; of those non-respondents, eight were men and 3 women; of those under 40 years, 16 responded compared with only three non-respondents; of those over 40 years, three responded versus eight non-respondents; as to the time elapsed between the onset of the disease and the beginning of anti-TNF, 14 (<2 years), one (2–5 years) and four (>5 years) responded, and five (<2 years), four (2–5 years) and two (>5 years) were non-respondents. Conclusion: There was no difference in response between the anti-TNF agents used; a better response was noted in those who used anti-TNF in combination with azathioprine, among women, in those under 40 years and in those treated within two years of the onset of the disease.